The analyse of how will the organisational factors influence the international retail companies' choice of entry mode when entering Chinese market. - Zhang, Yixin (2017)
After the Chinese ‘open policy’, the economic condition in China has experienced a dramatically increase. It made China become one of the most attractive market for international organisations. Meanwhile, with the fast development economic globalization and communication globalization, more and more international organisations tries to expand their business in China. The first and most important thing for organisations to decide is the market entry strategy, it will influence companies’ future objective. The entry strategy was divided into three main modes, export entry mode, contractual entry mode and investment entry mode. This research is focus on international retail organisations, analyse their internal factors which may or may not have impact on market entry strategy. Eight internal factors were chosen based on current theories, use data collected through email questionnaire to do logistic regression, and then analyse whether the eight factors have correlation with companies’ choice of entry mode. This research is very helpful for international organisations which trying to enter Chinese market, especially retail companies. The results and conclusion analysed through the research could guide organisations to decide their market entry strategy. Moreover, hopefully, this research will also provide a guidance for future researchers who are also interested in the same field.